Conditioning of Parsley (Petroselinum crispum L.) Suspension Cells Increases Elicitor-Induced Incorporation of Cell Wall Phenolics. - Kauss, H. (1993)
The elicitor-induced incorporation of phenylpropanoid derivatives into the cell wall and the secretion of soluble coumarin derivatives (phytoalexins) by parsley (Petroselinum crispum L.) suspension cultures can be potentiated by pretreatment of the cultures with 2,6-dichloroisonicotinic acid or derivatives of salicylic acid. To investigate this phenomenon further, the cell walls and an extracellular soluble polymer were isolated from control cells or cells treated with an elicitor from Phytophthora megasperma f. sp. glycinea. After alkaline hydrolysis, both fractions from elicited cells showed a greatly increased content of 4-coumaric, ferulic, and 4-hydroxybenzoic acid, as well as 4-hydroxybenzaldehyde and vanillin. Two minor peaks were identified as tyrosol and methoxytyrosol. The pretreatment effect is most pronounced at a low elicitor concentration. Its specificity was elaborated for coumarin secretion. When the parsley suspension cultures were preincubated for 1 d with 2,6-dichloroisonicotinic, 4- or 5-chlorosalicylic, or 3,5- dichlorosalicylic acid, the cells exhibited a greatly increased elicitor response. Pretreatment with isonicotinic, salicylic, acetylsalicylic, or 2,6-dihydroxybenzoic acid was less efficient in enhancing the response, and some other isomers were inactive. This increase in elicitor response was also observed for the above-mentioned monomeric phenolics, which were liberated from cell walls upon alkaline hydrolysis and for "lignin-like" cell wall polymers determined by the thioglycolic acid method. It was shown for 5-chlorosalicylic acid that conditioning most likely improves the signal transduction leading to the activation of genes encoding phenylalanine ammonia lyase and 4-coumarate: coenzyme A ligase. The conditioning thus sensitizes the parsley suspension cells to respond to lower elicitor concentrations. If a similar mechanism were to apply to whole plants treated with 2,6-dichloroisonicotinic acid, a known inducer of systemic acquired resistance, one can hypothesize that fungal pathogens might be recognized more readily and effectively.